Case 3733: Cetonia marmorea Olivier, 1789 (Coleoptera: Scarabaeidae: Cetoniinae: Gymnetini): proposed conservation by reversal of precedence with Scarabaeus pulcher Swederus, 1787 - Ratcliffe, Brett C (Bulletin of Zoological Nomenclature, 2017)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the widely used name Gymnetis marmorea (Olivier, 1789), a flower chafer (Scarabaeidae: Cetoniinae) from Trinidad and Tobago, West Indies, which is threatened by the unused senior subjective synonym Scarabaeus pulcher Swederus, 1787. The head of the holotype of Scarabaeus pulcher Swederus, 1787 is excluded from the holotype under Article 73.1.5 of the Code since it is a piece belonging to a Cotinis Burmeister glued to the body of a Gymnetis MacLeay.
Keywords: Nomenclature; taxonomy; Insecta; Coleoptera; Scarabaeidae; Cetoniinae; Cetonia marmorea; Gymnetis marmorea; Gymnetis pulchra; Gymnetosoma marmorea; Scarabaeus pulcher; Neotropics; flower chafer